SOSIALISASI UU ITE BAGI SISWA SMK ISLAM AL BAROKAH LAMPUNG TENGAH (Jurnal PkM Pemberdayaan Masyarakat, 2022)
The progress of communication and information technology deserves to be acknowledged. Sophistication is increasingly dominating the ladder of life that begins to move to an area without limits. Every progress does have a positive and negative effect. We just need to be aware and avoid negative effects. The rise of crimes in cyberspace such as the spread of viruses, fake news, violence, fraud, data theft, distribution of personal photos/videos, pornography, and so on is clear evidence that internet users must have sufficient knowledge about the dangers and anticipation so as not to become a victim of crime in cyberspace. cyberspace. The need for Central Lampung regional government in disseminating information through the Communications and Informatics Service to provide socialization of the ITE Law, this activity is motivated by a large number of young people, especially students who do not understand how to use social media properly and correctly, therefore it is necessary to be socialized about the ethics of using the internet, especially social media among school-age children. Based on these problems, this activity aims to provide an understanding to vocational students about the importance of ethics using internet media and social media.